The inhibiting effects of organic acids on arsenic immobilization by ferrihydrite: Gallic acid as an example. (July 2022) - Yang, Yongqiang; Rao, Xiongfei; Fu, Qingling; Zhang, Xin; Gao, Jieyu; Wan, Xiang; Zhu, Jun; Huang, Guoyong; Hu, Hongqing
Abstract: Organic acids usually compete the immobilization of As by iron (hydro)oxides, but their oxidizing effects are ignored. Therefore, the gallic acid (GA) with strong redox activity was chosen to investigate the influence of arsenite [As(III)] oxidation on As immobilization by ferrihydrite. Our results found that the As amount adsorbed on ferrihydrite decreased with the pH rising from 5 to 9 in the presence of GA, and the adsorption amount (28.8 g kg −1 ) at pH 9 was 45.1% lower than that in the absence of GA. Meanwhile, the As adsorption amounts in treatments of GA addition before As (Fh-GA-As(III)) were significantly lower than that in their corresponding simultaneous addition (Fh-As(III)/GA). The proportions of As(V)/Astotal on ferrihydrite and in equilibrium suspension were increased as the pH increased in the presence of GA, and the highest oxidation efficiency of As(III) by GA at pH 9 was 90.3%, which was mainly due to the contribution of hydrogen peroxide (H2 O2, 52.6%) and semiquinone radicals (SQ −, 27.1%). In general, the oxidation and competition adsorption of As by GA inhibited the As immobilization by ferrihydrite, and the oxidation of As(III) by GA was strongly dependent on pH, while H2 O2 and SQ − were demonstrated as the main oxidant at pH 9. Graphical abstract: Image 1 Highlights: As(III) was more likely to be oxidated by gallic acid (GA) in alkaline conditions. H2 O2 and SQ − were demonstrated as the main oxidants for As(III) oxidation. The oxidation As(III) by GA inhibited As immobilization by ferrihydrite. The competition adsorption of GA inhibited As immobilization by ferrihydrite.